Comparative study on the effects of nitrogen and carbon dioxide on methane/air flames. (1st July 2016) - Zhang, Chi; Hu, Ge; Liao, Shiyong; Cheng, Qian; Xiang, Chenxuan; Yuan, Chun
Abstract: The measurement of flame temperature profile and flame computation were conducted to analyze the effects of carbon dioxide and nitrogen dilution on methane/air flames. Results indicated that carbon dioxide addition shows more significant effects on the thermal properties of flame, except for flame thickness. Flame kinetic analyses were implemented for the heat release of individual reaction. It is suggested that the heat release contribution of dominant reaction is primarily affected by flame stoichiometry, while the dilution shows weak effect. The concentrations of reactive species play important influences on the progress rate of reaction. The peak product of reactive species concentrations of the dominant reactions could be approximated by an exponent expression of the concentration of initial reactants and dilution rate, and a greater exponential index was obtained for the flames with carbon dioxide addition. The emission indices and combustion efficiency were evaluated to assess the profit in NO suppression and the loss in combustion deterioration. Results indicated that the profit-loss ratio is influenced by both flame equivalence ratio and the component of diluent gas. For rich methane/air flame, nitrogen dilution shows a greater value, while a larger benefit is obtained for stoichiometric flame diluted by carbon dioxide. Highlights: Temperature measurement and flame modeling were made to study dilution effects. Carbon dioxide shows more significant effects on most of flame thermal properties. Carbon dioxide inhibits the formation of reactive intermediate significantly. Both flame stoichiometry and diluent affect the profit and the loss of dilution.